Problematika Manajemen Pondok Pesantren - Ghafur, Octa Abdul (Lembaga Yasin AlSys, 2024)
Islamic boarding schools are Islamic educational institutions that are full of learning about religious knowledge, such as classical books and other Shari'ah books. Islamic boarding schools are typical Indonesian educational institutions that grow amidst communities that have proven their independence. Pesantren has a meaning that continues to change along with its development over time. Islamic boarding schools can be defined as educational institutions as well as Islamic religious broadcasting institutions. In this case, the researcher discusses the problems found in Islamic boarding schools, including in the management system. The systematics of writing this paper uses the Library Research or Literature Review method, which has a research focus on books, journals and magazines related to the studies raised in the paper. There are various kinds of management problems in Islamic boarding schools, ranging from facilities, spatial planning, learning to the quality of teacher human resources. This research contributes to managerial learning literacy in Islamic boarding schools so that it can become a reference and reference.